Funhaler spacer: improving adherence without compromising delivery. Issue 7 (1st July 2003) - Watt, P M; Clements, B; Devadason, S G; Chaney, G M
Abstract : A novel asthma spacer device, the "Funhaler", incorporates incentive toys which are isolated from the main inspiratory circuit by a valve. Here we show that its use does not compromise drug delivery. Improved adherence combined with satisfactory delivery characteristics suggest that the Funhaler may be useful for management of young asthmatics.